Use of Speech on Whatsapp Social Media Study of Language Decity - Nur Halima Ahmad; Yusni Khairul Amri (BIRCU, 2023)
Politeness in language between parents and children in the family environment is highly prioritized even by using WA social media. The primary data used is the WAG of the Dahlan Family as much as 9 Scrennshot data consisting of 52 WA dialogue dialogues. Meanwhile, secondary data consists of books, journals, and other social media sources. To analyze the data, pragmatic theory was used which was put forward which focused on language politeness by Leech (1983:16). There are six types of politeness principles, namely: a) Tact maxim, b) Generosity maxim, c) Appreciation maxim, d) Simplicity maxim, e) Maxim of agreement, f) Maxim of sympathy. As for analyzing the data is done with the following steps. (1) Reading and viewing the contents of conversations on whatsapp social media, (2) Mark each conversation or sentence that contains forms of politeness, (3) Classify based on the types of politeness and politeness principles, (4) Summarize the data that has been presented carefully. Based on these data, after analyzing the results, there are six types of language politeness, namely: wisdom maxim found 10, generosity maxim found 7, appreciation maxim, modesty maxim, consensus maxim and sympathy maxim.